The Importance of colloids for the behavior of uranium isotopes in the low-salinity zone of a stable estuary - Andersson, P; Porcelli, D; Gustafsson, O; Ingri, J; Wasserburg, G (2001)
Particle-mediated removal processes of U isotopes were investigated during spring flood discharge in the low-salinity zone (LSZ, up to 3 practical salinity units [psu]) of a stable estuary. A shipboard ultrafiltration cross-flow filtration (CFF) technique was used to separate particles (>0.2 μm) and colloids (between 3000 daltons (3 kD) and 0.2 μm) from ultrafiltered water (<3 kD) containing "dissolved" species. Sediment traps were used to collect sinking material. Concentration of Fe and organic C, which are indicators of the major U carrier phases, were used to interpret the behavior of 234U- 238U during estuarine mixing. Colloids dominated the river water transport of U, carrying ≈90% of the U. On entering the estuary, colloids accounted for the dominant fraction of U to about a salinity of 1 psu, but only a minor fraction (<5%) at 3 psu. A substantial fraction of the total U is removed at <1 psu by Fe-organic rich colloids that aggregate and sink during initial estuarine mixing in the Kalix River estuary. In contrast, at salinities >1 psu, there is a general correlation between U and salinity in all filtered fractions. The 234U/ 238U ratios in different filtered fractions and sinking particles were generally indistinguishable at each station and showed enrichment in 234U, compared with secular equilibrium (δ 234U = 266-567). This clearly shows that all size fractions are dominated by nondetrital U. Consideration of U isotope systematics across the estuary reveals that substantial U exchange must occur involving larger particles at least to 1 psu and involving colloids at least to ≈ 1.5 psu. Further exchange at higher salinities may also occur, as the proportion of U on colloids decreases with increasing salinity. This may be due to decreasing colloid concentration and increasing stabilization of uranyl carbonated complexes during mixing in the estuary. The results show that although U is a soluble element that shows generally conservative mixing in estuaries, removal occurs in the very low salinity zone, and this zone represents a significant sink of U. Variation in composition and concentration of colloidal particles between different estuaries might thus be an important factor for determining the varying behavior of U between estuaries. Copyright © 2001 Elsevier Science Ltd.